Total Risk, Capital Structure, and Profitability Analysis: The Impact On Corporate Sustainability Mediated By Firm Performance - Elia Rossa; Adler Haymans Manurung; Nera Marinda Machdar (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This research aims to analyze the relationships among total risk, capital structure, and profitability, and their impact on corporate sustainability, with firm performance acting as a mediator. Corporate sustainability has become increasingly important in today’s competitive and dynamic business environment. A literature review indicates that well-managed total risk can enhance firm performance, while an optimal capital structure contributes to higher profitability. In turn, profitability enables companies to invest in innovation and sustainable development. This study identifies a gap in the existing literature, as few studies integrate these three factors within the context of sustainability. By employing a comprehensive analytical approach, this research seeks to provide deeper insights into how total risk, capital structure, and profitability interact to support corporate sustainability. The findings are expected to significantly contribute to financial management practices and sustainable corporate policies.